Extensor Tendon Injury Associated With Dorsal Entry Flexible Nailing of Radial Shaft Fractures in Children: A Report of 5 New Cases and Review of the Literature. Issue 4 (April 2019) - Murphy, Hamadi A.; Jain, Viral V.; Parikh, Shital N.; Wall, Eric J.; Cornwall, Roger; Mehlman, Charles T.
Abstract : Background: Extensor pollicis longus (EPL) tendon injury following the dorsal approach to elastic stable intramedullary nailing (ESIN) of the radius has been reported in a growing number of cases in the literature. This study includes 5 new cases from our institution as well as a comprehensive review of previously reported cases from the literature. Methods: We conducted a retrospective chart review of all patients undergoing ESIN between January 1, 2004 and December 31, 2013 at our institution. Those patients with an EPL injury or rupture were identified and clinical data collected included operative technique, diagnosis, treatment, and outcomes data. In addition, we performed a systematic review of the literature using Pubmed MEDLINE database, the Chochrane database, Scopus, Web of Science, and Embase. A total of 28 cases of EPL injury following ESIN of the radius were identified in the literature and the relevant data were extracted from those studies. Results: All 33 pediatric cases of EPL tendon injury occurred after entry to the radial canal was obtained by the dorsal approach to ESIN. EPL injury was diagnosed an average of 10 weeks following the index procedure. Extensor indicis pollicis to EPL transfer was performed in 13 patients, tendon release/lysis of adhesions in 5, EPL repair in 2, EPL graft reconstruction from palmaris longus tendon in 1, 3 patients refused further intervention, and treatment was unreported in 7 cases. By 12-month follow-up, all operatively treated patients had a good functional outcome with near anatomic extension at the thumb interphalangeal joint, no pain, and no further complication. Conclusions: EPL tendon injury was found to be a complication unique to the dorsal entry approach for ESIN of the radius. The lateral approach appears to offer a safer alternative with regard to the EPL tendon. We suggest that physicians consider the risk of EPL tendon injury when planning for ESIN of the radius, and make an effort to avoid direct injury when using a dorsal approach. Level of Evidence: Level III—therapeutic.